Metastatic Pancreatic Adenocarcinoma Presenting as a Klatskin Tumor. Issue 1 (2018) - Munis, Assad; Omar, Hina; Iwaz, Suzanne; Mahdavian, Mani
ABSTRACT : N/A: Cholangiocarcinoma is a rare clinical entity representing approximately 2% of all cancers diagnosed. More than 65% of these tumors can present at the bifurcation of the hepatic duct and are known as Klatskin tumors. Pancreatic cancer is among the top 5 leading causes of cancer death, and it usually presents at an advanced stage with metastasis commonly seen in the liver. We report a patient with established pancreatic adenocarcinoma who presented with an obstructing mass at the hepatic duct bifurcation without any prior history of biliary tract disease. This represents a new diagnosis of either intracholedochal metastatic tumor or a new diagnosis of cholangiocarcinoma found at the hepatic duct bifurcation without liver involvement in the setting of pancreatic cancer, suggesting metachronous cholangiocarcinoma with pancreatic adenocarcinoma.